Enhanced Performance of High-Power InAs/GaAs Quantum Dot Lasers Through Indium Flushing - Deyan Dai; Hanqing Liu; Xiangjun Shang; Shizhuo Tan; Qiaozhi Zhang; Chengao Yang; Dongwei Jiang; Xiangbin Su; Haiqiao Ni; Zhichuan Niu (Photonics)
InAs/GaAs quantum dots (QDs) appear promising for optoelectronic applications. However, the inhomogeneous broadening caused by natural strain and the non-uniform size distribution deteriorates the device performance based on multi-stacked QD layers. In this study, In-flush was incorporated during the epitaxy, and the photoluminescence (PL) linewidth was significantly narrowed to 26.1 meV for the flushed sample and maintained to 27.3 meV for the unflushed sample. The flushed sample shows better device performance in threshold current (0.229 to 0.334 A at 15 °C), power (1.142 to 1.113 W at 15 °C), and characteristic temperature (51 to 39 K in the range of 55~80 °C) compared with the unflushed sample.